A multidisciplinary approach to authentic learning experiences for nature-based solutions design: broadening the monkey cheeks. Issue 1 (2nd January 2022) - Irvine, Kim; Likitswat, Fa; Suwanarit, Asan; Koottatep, Thammarat
ABSTRACT: Students in a Landscape Architecture studio at Thammasat University and an Environmental Engineering class at Asian Institute of Technology joined to develop and assess Nature-based Solution designs for a pond/wetland system in peri-urban Bangkok. The Landscape Architecture class first developed their design visions and subsequently their designs were introduced to the Engineering students through on-line presentations and collaborative on-site investigations. The Engineering students used combinations of water quality sampling, static calculations, and application of a conceptual, dynamic urban hydrology model to assess design performance. The Engineering students effectively incorporated some aspects of the architectural designs into their assessments, particularly those related to constructed wetlands for water quality improvement. Application of the dynamic model for water quantity assessments and provision of project cost estimates proved more challenging. Course evaluations indicated that students in both classes gained a better appreciation of the multidisciplinary process necessary for successful water resource planning, but also would prefer even greater interaction between the disciplines. Planned pedagogical improvements, including introduction of Steinitz' Framework for Theory, are discussed.